Insulin and glucose homeostasis in childhood cancer survivors treated with abdominal radiation: A pilot study. Issue 11 (15th July 2018) - Friedman, Danielle Novetsky; Hilden, Patrick; Moskowitz, Chaya S.; Wolden, Suzanne L.; Tonorezos, Emily S.; Antal, Zoltan; Carlow, Dean; Modak, Shakeel; Cheung, Nai‐Kong; Oeffinger, Kevin C.; Sklar, Charles A.
Abstract: Background: Childhood cancer survivors exposed to abdominal radiation (abdRT) are at increased risk for both insulin‐dependent and non–insulin‐dependent diabetes. We sought to clarify the pathophysiology of diabetes after abdRT by performing dynamic studies of insulin and glucose and testing for type 1 diabetes‐associated autoantibodies. Procedure: Cross‐sectional analysis of 2‐year childhood cancer survivors treated with abdRT at age ≤21 years who underwent oral glucose tolerance testing and assessment of diabetes‐related autoantibodies from December 2014 to September 2016. Prevalence of insulin/glucose derangements, indices of insulin sensitivity/secretion (homeostatic model assessment of insulin resistance [HOMA‐IR], whole‐body insulin sensitivity, insulinogenic index), autoantibody positivity, and treatment/demographic factors associated with adverse metabolic outcomes were assessed. Results: Among 40 participants previously exposed to abdRT (57.5% male; median age at cancer diagnosis, 3.3 years [range, 0.5–20.1]; median age at study 14.3 years [range, 8.3–49.8]; none with obesity), 9 (22.5%) had glucose derangements ( n  = 4 with impaired fasting glucose [≥100 mg/dL]; n  = 4 with impaired glucose tolerance [2‐hour glucose 140–199 mg/dL]; n  = 1 with previously unrecognized diabetes [2‐hour glucose ≥200 mg/dL]). Three of the four individuals with impaired fasting glucose also had insulin resistance, as measured by HOMA‐IR; an additional four subjects with normal glucose tolerance were insulin resistant. The subject with diabetes had normal HOMA‐IR. No participant had absolute insulinopenia or >1 positive diabetes‐related autoantibody. Conclusions: This study suggests that radiation‐induced damage to the insulin‐producing β‐cells is an unlikely explanation for the early derangements in glucose metabolism observed after abdRT. Research into alternative pathways leading to diabetes after abdRT is needed.